ADDIE MODEL: PENGEMBANGAN MEDIA LIKURDIN PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Nanda Nitami; Nazliati Nazliati; Rita Sari (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
Islamic cultural history is one of the subjects that is considered boring. Using media can be an alternative to help the learning process to be more enjoyable. Likurdin is the media that modified the form of monopoly and the History of Khulafaurrasyidin. Developing this media aims to produce learning media on Khulafaurrasyidin History material and determine Likurdin media's effectiveness. This research uses the R&D (Research and Development) method with the ADDIE development model developed by Dick and Carry (1996) with 5 (five) stages, namely analysis, design, development, implementation, and evaluation. Data collection techniques through media expert validator sheets, material experts, and student questionnaire sheets. Based on the results of the study, after being validated by validators from 2 teams of experts, namely media experts at 96% and material experts at 100%, which means that Likurdin learning media is "very effective" to be developed. Student responses to Likurdin learning media also obtained "very interesting" criteria with a percentage of 93%.Sejarah kebudayaan Islam merupakan salah satu mata pelajaran yang dianggap membosankan. Penggunaan media pembelajaran dapat menjadi alternative dalam membantu proses pembelajaran untuk lebih menyenangkan. Media pembelajaran Likurdin adalah media modifikasi berbentuk monopoli yang menyajikan materi Sejarah Khulafaurrasyidin. Tujuan pengembangan media ini yaitu untuk menghasilkan media pembelajaran pada materi Sejarah Khulafaurrasyidin dan untuk mengetahui keefektifan media Likurdin. Penelitian ini menggunakan metode R&D (Research and Developmen) dengan model pengembangan ADDIE yang dikembangkan oleh Dick and Carry (1996) dengan 5 (lima) tahap, yaitu analisis (analysis), desain (design), pengembangan (development), implementasi (implementation),Â Â dan evaluasi (evaluation). Teknik pengumpulann data melalui lembar validator ahli media dan ahli materi, serta lembar angket peserta didik. Berdasarkan hasil penelitian, setelah divalidasi oleh validator dari 2 tim ahli yaitu ahli media sebesar 96% dan ahli materi sebesar 100% yang berarti bahwa media pembelajaran Likurdin â€œsangat efektifâ€ untuk dikembangkan. Respon siswa terhadap media pembelajaran Likurdin juga diperoleh kriteria â€œsangat menarikâ€ dengan persentase sebesar 93%.